Influence of track structure and condensed history physics models of Geant4 to nanoscale electron transport in liquid water. (February 2019) - Kyriakou, I.; Ivanchenko, V.; Sakata, D.; Bordage, M.C.; Guatelli, S.; Incerti, S.; Emfietzoglou, D.
Highlights: The electromagnetic physics models of Geant4 v10.4 have been compared for nanoscale electron transport. Livermore offers the best performance among the condensed-history models. Livermore is the least sensitive to variation of stepsize limit but the most sensitive to the tracking cut. Differences between condensed-history and discrete models is significant for sub-keV electrons and/or nanometer targets. Abstract: The Geant4 toolkit offers a range of electromagnetic (EM) models for simulating the transport of charged particles down to sub-keV energies. They can be divided to condensed-history (CH) models (like the Livermore and Penelope models) and the track-structure (TS) models included in the Geant4-DNA low-energy extension of Geant4. Although TS models are considered the state-of-the-art for nanoscale electron transport, they are difficult to develop, computationally intensive, and commonly tailored to a single medium (e.g., water) which prohibits their use in a wide range of applications. Thus, the use of CH models down to sub-keV energies is particularly intriguing in the context of general-purpose Monte Carlo codes. The aim of the present work is to compare the performance of the CH models of Geant4 against the recently implemented TS models of Geant4-DNA for nanoscale electron transport. Calculations are presented for two fundamental quantities, the dose-point-kernel and the microdosimetric lineal energy. The influence of user-defined simulation parameters (tracking and production cuts, and maximum step size) on the above calculations is also examined. It is shown that Livermore offers the best performance among the CH models of Geant4 for nanoscale electron transport. However, even under optimally-chosen simulation parameters, the differences between the CH and TS models examined may be sizeable for low energy electrons (<1 keV) and/or nanometer size targets (<100 nm).